Planetary Terrestrial Analogues Library project: 1. characterization of samples by near-infrared point spectrometer. (15th September 2020) - Lantz, C.; Poulet, F.; Loizeau, D.; Riu, L.; Pilorget, C.; Carter, J.; Dypvik, H.; Rull, F.; Werner, S.C.
Abstract: The PTAL project aims at building and exploiting a database involving several analytical techniques, the Planetary Terrestrial Analogues Library, to help characterizing the mineralogical evolution of terrestrial bodies, starting with Mars. A total of 94 natural Earth rocks have been collected from selected locations around the world to get a selection of analogues for Martian geology. The PTAL library gathers a variety of igneous rocks from different plutonic and volcanic origins and compositions, associated to different environments and levels of aqueous alteration. Samples of impact craters and sedimentary units are also present. The full set of samples will be characterized with optical thin section analysis and XRD (Oslo University, Norway), NIR spectroscopy (Paris-Saclay University, France), Raman spectroscopy (Valladolid University, Spain) and LIBS (Paul Sabatier University, France). The multianalytical study used within the PTAL project provides an unique opportunity to coordinate minerals/elements detection by different techniques that are similar to the instruments onboard current and forthcoming Martian missions. Such combined analysis should give the opportunity to prepare and improve ExoMars/ESA-Roscosmos and Mars2020/NASA observations. This paper focuses only on the NIR measurements and interpretations. The diversity of the PTAL samples is well revealed by the diversity of spectra from the NIR observations. The detected minerals are representative of various formation, alteration and geochemical environments. The major diagnostic features observed are those of primary Fe 2+ bearing silicates like olivine or pyroxene with low and/or high calcium content; altered silicates detected with vibrational features associated to OH and/or H2 O and/or metal-OH features; oxides; zeolites; and carbonates. This collection brings together a set of rocks and minerals that have been reported elsewhere in the Solar System and particularly on Mars. Highlights: Building a NIR spectral library to support planetary surface exploration. Measurements on Mars analogues: rock specimens instead of pure minerals. Interpretations of the spectra and relevance compared to Mars geological settings. Need of multi technique analysis to better constrain mineralogy.